Binding and Smiting: One More Merism in Luvian Incantations - Melchert, Harold Craig (JAOS, 2022)
The purpose of this paper is to offer evidence for a set of related formulaic expressions meaning ‘bond and blow’, ‘of binding and smiting’, and ‘the substitute for binding and smiting’ in Luvian cuneiform texts of the second millennium bCe. The passages where the relevant formulae are attested have resisted a coherent interpretation thus far. Our argumentation is three-pronged. First, we resort to the combinatorial method to show that these formulae occur in the vicinity of other merisms, and therefore are likely to constitute the same figure of speech. Further- more, we endeavor to demonstrate based on context that they denote something related to strong physical impact. The argument involves a great deal of restored text, but although voluminous, the contexts are so repetitive that the restorations appear warranted. Second, we use the etymological method in order to justify the claim that the roots supplying their reflexes to our formulae are Proto-Indo- European *seh2 ‘to bind’ and *wedh ‘to strike, smite’. The derivation of each of the derivatives occurring in the bipartite merisms under discussion is addressed in some detail, and additional evidence from a Luwian hieroglyphic inscription kululu 1 is adduced to flesh out our hypothesis. Third, we provide typological discussion facilitating the interpretation of "binding" and "smiting" in the context of the Hittite-Luvian antiwitchcraft rituals. It turns out that hostile witchcraft has a potential to both "bind" (paralyze) and "smite" (cause to suffer) the body parts of its victim. As a whole, the paper represents a contribution to the ongoing decipher- ment of the Luvian language.